Transfusion medicine competency andthe fundaments for its implementation in Anesthesiology and Reanimation - Fernández Franch, Neyda; Torres Romo, Ubaldo Roberto; Menéndez Cabezas, Arturo Teodoro; López Lazo, Sarah Estrella; Liza Hernández, Oscar (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: A way to overcome the blood transfusion disadvantages is determining and developing transfusion competencies. Objective:The research aims were to identify the elements of transfusion medicine competencyand todescribe the fundaments for its implementation inthe specialty of Anesthesiology and Reanimation.Materials and Methods:Transfusion competencies include, among others, knowledge of the risks of blood-borne infections, safe prescription of blood products, identification of transfusion reactions, and competently perform and teach undergraduates the procedure of intravenous infusion of blood and blood products. It alsoincludesknowing and updating on ethical, scientific and legal issuesof blood components transfusion. Results:In Anesthesiology and Reanimation, transfusion medicine competency also involves demonstration of knowledge, abilities and values for the preoperative preparation of the patients with anemia, bleeding risk and other hematological illnesses, for the use of pharmacological and non pharmacological alternatives, as well as for blood components’ economy. Conclusions:Being competent in transfusional medicine in this specialty impliesan important and substantial reduction of the general morbidity-mortality andparticularly thatassociated with transfusion complications, and requires the capacity of mobilizethe set of knowledge, skills, attitudes and values in a comprehensiveand pertinent way in order to transfuse less and better, with more safety and lessexpenditures.